Spatially resolving amplitude and phase of light with a reconfigurable photonic integrated circuit - Buetow, Johannes; Eismann, Joerg S.; Milanizadeh, Maziyar; Morichetti, Francesco; Melloni, Andrea; Miller, David A. B.; Banzer, Peter (Optica, 2022)
Photonic integrated circuits play a pivotal role in many applications. Particularly powerful are circuits based on meshes of reconfigurable Mach-Zehnder interferometers as they enable active processing of light. This meets demands accross different fields, from communication to signal and information processing and sensor applications. Here, we use a reconfigurable photonic integrated circuit to realize a spatially resolving detector of amplitudes and phases of an electromagnetic field distribution. This is achieved by optically sampling free-space beams with a carefully designed input interface and subsequently processing the resulting on-chip light within the photonic mesh of interferometers. To perform measurements of this kind, we develop and experimentally implement a versatile method for the calibration and operation of such integrated photonics based detectors. Our technique works in a wide parameter range, even when running the chip off the design wavelength. Amplitude, phase, and polarization sensitive measurements are of enormous importance in modern science and technology, providing a vast range of applications for such integrated detectors. (C) 2022 Optica Publishing Group under the terms of the Optica Open Access Publishing Agreement
CRIS-Team WoS Importer:2022-09-02